1986
DOI: 10.1021/ma00156a049
|View full text |Cite
|
Sign up to set email alerts
|

Thermoselective permeation from a polymer-grafted capsule membrane

Abstract: Communications to the Editor Thermoselective Permeation from a Polymer-Grafted Capsule Membrane1,2 Permeability of microcapsules has been investigated rather extensively because of its importance in the design and construction of sustained drug release devices and artificial cells.3,4 In spite of its potential usefulness, the reversible, signal-receptive permeation control of the capsule has not been fully investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
79
2

Year Published

1998
1998
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(81 citation statements)
references
References 1 publication
0
79
2
Order By: Relevance
“…27 Okahata et al developed pH-and temperatureresponsive polymer-grafted porous nylon capsule membranes with large diffusional permeability changes (up to a factor of 225). 3,28 They reported that the permeability response was not affected by graft yield ranging from 35 to 275% when hydrophobic poly(4-vinyl pyridine) was grafted. In contrast, when the graft polymer was relatively hydrophilic, the pH response decreased with increasing graft yield.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…27 Okahata et al developed pH-and temperatureresponsive polymer-grafted porous nylon capsule membranes with large diffusional permeability changes (up to a factor of 225). 3,28 They reported that the permeability response was not affected by graft yield ranging from 35 to 275% when hydrophobic poly(4-vinyl pyridine) was grafted. In contrast, when the graft polymer was relatively hydrophilic, the pH response decreased with increasing graft yield.…”
Section: Introductionmentioning
confidence: 98%
“…19,20 Temperature-, pH-or photosensitive polymers have been grafted onto porous substrates. [2][3][4][5]7,[11][12][13][14] The grafted polymers may be located mainly on the external membrane surface, 2,12 or they may be on the external surface as well as inside the pores, 4,7,14 depending on the grafting conditions. For example, in some reports of plasma-induced graft polymerization, active species for initiating are generated mainly near the membrane sur-face, resulting in preferential surface grafting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apparently opposite temperature dependence of tryptophan permeation was found with these membranes. A number of signal-responsive polymer membranes have been prepared, but the mechanism of signal responsiveness was not made perfectly clear [26,46]. Although Iwata et al [47] and the author proposed a thermosensitive permeation mechanism, the explanations did not stand on the experimental results using the same material.…”
Section: Thermosensitive Polymer-grafted Porous Membranementioning
confidence: 82%
“…Among the chemical techniques used to prepare thermo-responsive membranes, one of the most common methods is the grafting of thermo-responsive polymers onto porous membrane substrates by different grafting techniques, such as plasma induced grafting [1][2][3][4][5][6][7][8][9][10], UVor 60 Co c-radiation induced grafting [11-17, 30, 31, 43-45], and other chemical grafting methods [20]. Another chemical approach to prepare thermoresponsive membranes involves two steps, i.e., firstly fabricating the thermo-responsive polymers by chemical grafting, and then preparing membranes using the fabricated polymers by the phase inversion method [18,19].…”
Section: Introductionmentioning
confidence: 99%